AgeWell.de – study protocol of a pragmatic multi-center cluster-randomized controlled prevention trial against cognitive decline in older primary care patients - Zülke A; Luck T; Pabst A; Hoffmann W; Thyrian JR; Gensichen J; Kaduszkiewicz H; König H-H; Haefeli WE; Czock D; Wiese B; Frese T; et al. (BioMed Central Ltd, 2019)
Background In the absence of treatment options, the WHO emphasizes the identification of effective prevention strategies as a key element to counteract the dementia epidemic. Regarding the complex nature of dementia, trials simultaneously targeting multiple risk factors should be particularly effective for prevention. So far, however, only few such multi-component trials have been launched, but yielding promising results. In Germany, comparable initiatives are lacking, and translation of these complex interventions into routine care was not yet done. Therefore, AgeWell.de will be conducted as the first multi-component prevention trial in Germany which is closely linked to the primary care setting. Methods AgeWell.de will be designed as a multi-centric, cluster-randomized controlled multi-component prevention trial. Participants will be older community-dwelling general practitioner (GP) patients (60–77 years; n = 1,152) with increased dementia risk according to CAIDE (Cardiovascular Risk Factors, Aging, and Incidence of Dementia) Dementia Risk Score. Recruitment will take place at 5 study sites across Germany. GP practices will be randomized to either intervention A (advanced) or B (basic). GPs will be blinded to their respective group assignment, as will be the statistician conducting the randomization. The multi-component intervention (A) includes nutritional counseling, physical activity, cognitive training, optimization of medication, management of vascular risk factors, social activity, and, if necessary, further specific interventions targeting grief and depression. Intervention B includes general health advice on the intervention components and GP treatment as usual. We hypothesize that over the 2-year follow-up period the intervention group A will benefit significantly from the intervention program in terms of preserved cognitive function/delayed cognitive decline (primary outcome), and other relevant (secondary) outcomes (e.g. quality of life, social activities, depressive symptomatology, cost-effectiveness). Discussion AgeWell.de will be the first multi-component trial targeting risk of cognitive decline in older adults in Germany. Compared to previous trials, AgeWell.de covers an even broader set of interventions suggested to be beneficial for the intended outcomes. The findings will add substantial knowledge on modifiable lifestyle factors to prevent or delay cognitive decline. Trial registration German Clinical Trials Register (reference number: DRKS00013555).
Keywords: Cluster-randomized controlled trial; Cognition; Dementia; Late life; Lifestyle; Mental health; Multi-component intervention; Prevention; Primary care; Aged; Aging; Behavior Therapy; Cognitive Dysfunction; Exercise; Female; Germany; Humans; Male; Middle Aged; Primary Health Care; Quality of Life; Risk Reduction Behavior